"I couldn't have done it alone" / Interview with Elena Gorol - Sadílková, Helena; Viková, Lada (Romano džaniben, 2024)
The interview provides an in-depth look at the experiences and views of Elena Gorolová, a well-known Romani activist who has campaigned for the recognition of forced sterilisation crimes and for compensation for the victims of these practices. These illegal procedures were conducted en masse particularly targetting Romani women in socialist Czechoslovakia, and subsequently in the Czech Republic and Slovakia, until the early 2000s. The law enabling their compensation was enacted in the Czech Republic only in 2021. In the interview, the acclaimed activist speaks openly not only about her own traumatic experience with the sterilisation practices, but also about her long fight for recognition and redress, which she has been leading since 2005. She discusses the sources of her inspirational yet personally demanding activism, and the intense debates and dilemmas she has faced with regard to her family, community, and fellow activists.